Non-invasive Brain Stimulation for Gambling Disorder: A Systematic Review - Zucchella, Chiara; Mantovani, Elisa; Federico, Angela; Lugoboni, Fabio; Tamburin, Stefano (Frontiers in Neuroscience, 2020)
Background. Gambling disorder (GD) is the most common behavioral addiction and shares pathophysiological and clinical features with substance use disorders (SUDs). Effective therapeutic interventions for GD are lacking. Non-invasive brain stimulation (NIBS) may represent a promising treatment option for GD. Objective. This systematic review aimed to provide a comprehensive and structured overview of studies applying NIBS techniques to GD and problem gambling. Methods. A literature search using Pubmed, Web of Science and Science Direct was conducted from databases inception to December 19th, 2019 for studies assessing the effects of repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (t-DCS) on subjects with GD or problem gambling. Studies using NIBS techniques on healthy subjects and those without therapeutic goals but only aiming to assess basic neurophysiology measures were excluded. Results. A total of 269 articles were title and abstract screened, 13 full texts were assessed and 11 were included, of which six were controlled and five were uncontrolled. Most studies showed a reduction of gambling behavior, craving for gambling and gambling-related symptoms. NIBS effects on psychiatric symptoms were less consistent. A decrease of the behavioral activation related to gambling was also reported. Some studies reported modulation of behavioral measures (i.e., impulsivity, cognitive and attentional control, decision making, cognitive flexibility). Studies were not consistent in terms of NIBS protocol, site of stimulation, clinical and surrogate outcome measures, and duration of treatment and follow-up. Sample size was small in most studies. Conclusions. The clinical and methodological heterogeneity of the included studies prevented us to draw any firm conclusion on the efficacy of NIBS interventions for GD. Further methodologically sound, robust and well-powered studies are needed.